Bridging Literacies with Videogames
XXIV, 210 p.
Keywords: Bridging Literacies with Videogames provides an international perspective of literacy practices, gaming culture, and traditional schooling. Featuring studies from Australia, Colombia, South Korea, Canada, and the United States, this edited volume addresses learning in primary, secondary, and tertiary environments with topics related to: • re-creating worlds and texts • massive multiplayer second language learning • videogames and classroom learning These diverse topics will provide scholars, teachers, and curriculum developers with empirical support for bringing videogames into classroom spaces to foster meaning making. Bridging Literacies with Videogames is an essential text for undergraduates, graduates, and faculty interested in contemporizing learning with the medium of the videogame.